2017
DOI: 10.4103/jmp.jmp_131_16
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the electronic portal imaging device for small radiation field measurements

Abstract: Purpose:With the advent of state-of-the-art treatment technologies, the use of small fields has increased, and dosimetry in small fields is highly challenging. In this study, the potential use of Varian electronic portal imaging device (EPID) for small field measurements was explored for 6 and 15 MV photon beams.Materials and Methods:The output factors and profiles were measured for a range of jaw-collimated square field sizes starting from 0.8 cm × 0.8 cm to 10 cm × 10 cm using EPID. For evaluation purpose, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Additionally, EPIDs over-respond to low-energy photons, 49 and have a dose rate dependence. 50 Studies with EPIDs have shown 16-23% errors in output factors for small field size (~8 mm 2 x 8 mm 2 ) in one study 51 and ~8% difference to film for measurements of small target plans (~3 mm 2 x 3 mm 2 ) in another. 50 Without appropriate correction of these dependencies, 4,52 errors may be present.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, EPIDs over-respond to low-energy photons, 49 and have a dose rate dependence. 50 Studies with EPIDs have shown 16-23% errors in output factors for small field size (~8 mm 2 x 8 mm 2 ) in one study 51 and ~8% difference to film for measurements of small target plans (~3 mm 2 x 3 mm 2 ) in another. 50 Without appropriate correction of these dependencies, 4,52 errors may be present.…”
Section: Introductionmentioning
confidence: 98%
“…EPID based dosimetry was recently investigated for small field sizes (down to 2x2cm 2 ) using a conventional linac [84] . Other groups have implemented portal dosimetry for VMAT SBRT treatments [85] , [86] .…”
Section: Phantom-less Methods For Dosimetry Auditsmentioning
confidence: 99%
“…22,[30][31][32][33][34][35] In recent years, the use of the electronic portal imaging device (EPID) for pre-treatment patient-specific treatment plan verification has gained increased interest due to its simplicity. 22,23,[26][27][28][29][35][36][37][38][39] The Varian EPID has been shown to be capable of producing high-resolution measured dose digital images which can be compared with predicted portal dose images calculated by the Eclipse TM Treatment Planning System (TPS) based on the actual fluence distribution for every patient treatment plan fields. 22,23,[28][29][30]36,40,41 Various methods including the dose difference (DD), distance-to-agreement (DTA) and the gamma (γ) index have been used to compare the measured and predicted dose images.…”
Section: Introductionmentioning
confidence: 99%
“…22,23,[28][29][30]36,40,41 Various methods including the dose difference (DD), distance-to-agreement (DTA) and the gamma (γ) index have been used to compare the measured and predicted dose images. [22][23][24][26][27][28][29][30][35][36][37][38][39][42][43][44] The DD is the difference in dose at a specified point in each of the predicted and measured dose distributions, and it is reflected as a percentage of the maximum dose, whereas the DTA represents the nearest distance between two points of equal dose on the predicted and measured dose images when superimposed. 22,23,30,42,43,45 According to Low et al 42 and Low & Dempsey, 43 the DD method is very sensitive in areas of high-dose gradient and a small spatial misalignment will cause a large DD between the measured and the calculated dose distributions, whereas the DTA method is sensitive in areas of low-dose gradient and a small DD in low-dose area could result in large DTA values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation